The impact of malnutrition, inflammation on cognitive impairment in hemodialysis patients-A multicenter study - Yuqi Yang; Jingjing Da; Qian Li; Yanjun Long; Jing Yuan; Yan Zha (Kidney & Blood Pressure Research, 2022)
Introduction: Cognitive impairment is prevalent in patients undergoing hemodialysis (HD), which is related to the nutritional and inflammatory status of this population. Malnutrition-inflammation score (MIS) has been identified as a useful tool to evaluate nutrition and inflammation status. The aim of this study is to investigate the association between MIS and cognitive impairment in HD patients. Methods: This was a multicenter observational cohort study with 1591 patients undergoing HD. Nutritional and inflammatory status was evaluated with MIS, anthropometric measurements, and body composition assessments. Cognitive function was evaluated with the Mini Mental State Examination (MMSE). The associations between MIS and cognitive impairment were analyzed by multivariable logistic regression models. Results: Among 1591 HD patients, the mean MIS was 6.0±2.6. Patients with higher MIS had significantly lower MMSE scores. 311 patients had cognitive impairment. After adjusting clinical confounders, higher MIS was independently associated with increased rate of cognitive impairment both as a categorized variable (OR, 1.358; 95%CI, 1.010-1.825; P=0.045) and as a continuous variable (OR, 1.113; 95%CI, 1.053-1.178; P<0.001). Subgroup analysis showed a stronger association between MIS and cognitive impairment in males, the population with age 41-60 years, and 61-80 years, no smoker, living by oneself, HD combined with or without hemoperfusion as dialysis modality. ROC curve analysis of MIS showed 60.1% sensitivity and 52.0% specificity in predicting cognitive impairment (AUC 0.604; 95%CI 0.567-0.640, P<0.001). Conclusions: MIS was an independently associated with cognitive impairment in HD patients.